RISK MANAGEMENT IN THE PROVISION OF PEOPLE’S BUSINESS CREDIT AS IMPLEMENTATION OF PRUDENTIAL PRINCIPLES - Hari Sutra Disemadi (Diponegoro Law Review, 2019)
The bank is a financial institution that has an intermediary function that bridges the interests of parties who are excess funds (creditors) and those who need funds (debtors). Banks in channeling funds, among others, through the provision of credit to the public. However, loans issued by banks contain a lot of risk, one of them is People's Business Credit (KUR). Issues regarding the risks of granting credit above will be discussed in this study, which this study uses a normative juridical method using the statutory approach. This study shows the arrangements regarding risk management are regulated in PBI Number 11/25/PBI/2009 concerning the Application of Risk Management in Commercial Banks and in Regulation of the Financial Services Authority Number 18 / POJK.03 / 2016 Regarding the Implementation of Risk Management for Commercial Banks. The implementation of the prudential principle internally for a bank's Human Resources (HR) is to apply the Banking Risk Management Principles. Banking practices usually assess five aspects of debtors (the five C’s analysis), namely: character, capital, capacity, economic conditions and collateral.